Accurate prediction of NOx emissions from diesel engines considering in-cylinder ion current. (November 2020) - Mohammadi, Milad; Neshat, Elaheh
Abstract: The main purpose of current study is accurate prediction of NOx emissions from diesel engines considering in-cylinder ion current. To reach this goal, a validated thermodynamic multi-zone model was used. A modified chemical kinetics mechanism of diesel fuel oxidation was used too. A chemical kinetics mechanism of NOX formation including 103 reactions was added to the main mechanism. A set of ions and ionic reactions was added to the developed chemical kinetics mechanism and finally a modified chemical kinetics mechanism with 445 reactions and 100 species was formed. The developed mechanism was coupled to the multi-zone model and a diesel engine was simulated. The importance of Zeldovich mechanism, prompt mechanism, N2 O mechanism and NNH mechanism were investigated. The progress rates of reactions were calculated and important reactions were identified. The results show that the oxygenated ions, NO +, O + and O2 +, has more effects on NO production than other ions. The prompt mechanism plays an important role in predicting the ion current inside the chamber. Because this mechanism has reactions that can lead to CH production. The CH radicals produced by this mechanism can be employed by basic ionic reactions and lead to ion production. The results show that using NOx related ionic reactions results in accurate prediction of engine exhaust NOx. Graphical abstract: This paper has been recommended for acceptance by Pavlos Kassomenos. Image 1 Highlights: NOx formation in diesel engines is simulated using ionic reactions. Using NOx related ionic reactions results in accurate prediction of exhaust NOx. CH plays an important role in initiating ionic reactions. The oxygenated ions, NO +, O + and O2 +, has significant effects on NO production.